Foundations of Islamic Resources Management - Shiva Alipour , Dr. Majid Zamahani, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In the age of globalization and rapid technological advancement, human capital has become a most important capital of organizations. Human capital is a set of skills, knowledge and general characteristics of people in the organization and can indicate their current activity and their potential for future. In order to use and manage human capital optimally in organizations, from the first quarter of the twentieth century, the field of personnel management as human resources management evolved. Due to the importance and necessity of Islamic resources management in this research, we explained the principles of Islamic management through library studies.